PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN MEDIA KONKRET UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI PENJUMLAHAN DAN PENGURANGAN SISWA KELAS II SD - Ni Kadek Srisedani; Ni Putu Intan Pratiwi; I Made Sujana Adnyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ mathematics learning outcomes on addition and subtraction material through the implementation of the Contextual Teaching and Learning (CTL) model assisted by concrete media for second grade elementary school students. This research was motivated by the low learning outcomes of students in mathematics subjects caused by difficulties in understanding abstract mathematical concepts, low student participation during the learning process, and the limited use of instructional media by teachers. The research method used was Classroom Action Research conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were second grade students at an elementary school. Data collection techniques were carried out through observation, tests, interviews, and documentation. The results of the study showed that the implementation of the Contextual Teaching and Learning model assisted by concrete media was able to improve students’ mathematics learning outcomes significantly. Students became more active, enthusiastic, confident, and able to understand addition and subtraction concepts more easily because the learning process was connected to real-life situations and supported by concrete objects around them. The improvement could be seen from the increase in students’ average scores and learning mastery in each cycle. Therefore, the CTL model assisted by concrete media can be used as an effective and innovative learning alternative to improve mathematics learning outcomes in elementary schools.